How to improve university-enterprise cooperation: application of intuitionistic fuzzy multi-attribute decision-making method based on decision-maker preferences in university-enterprise cooperation satisfaction evaluation - Zhang, Ye; Zhang, Ziqun; Chen, Xinrong (Frontiers in Education, 2025)
IntroductionUniversity-enterprise cooperation (UEC) is critical for bridging the gap between higher education and industry, enhancing student employability and professional readiness. However, assessing the quality of such cooperation from the student perspective remains a challenge due to subjective uncertainty and varying attribute importance.MethodsThis study, conducted at universities of applied sciences in China, developed an intuitionistic fuzzy multi-attribute decision-making (IFMADM) model to evaluate student satisfaction with UEC. The model integrates intuitionistic fuzzy sets and intuitive fuzzy entropy to handle ambiguity in student responses and to determine the relative importance of cooperation attributes.ResultsBased on survey data from 290 postgraduate students, the analysis revealed that satisfaction with guidance from university and enterprise mentors during enterprise practice significantly impacts overall student satisfaction. Among the evaluated attributes, university tutor guidance received the highest weight.DiscussionThe findings highlight the central role of mentorship in shaping student experiences in UEC. Enhancing guidance mechanisms—particularly from university tutors—can effectively improve the quality and effectiveness of cooperation. The proposed model offers a robust evaluation framework and practical insights for optimizing student-centered UEC practices.